Environmental DNA Detects Endangered Texas Hornshell and Its Hosts - Daniel H. Mason; Heidi A. Henderson; Thomas W. Franklin; Michael K. Young; Jennifer E. Hernandez; Cory L. Engkjer; Joanna Hatt; Michael K. Schwartz (Ecology and Evolution)
ABSTRACT Environmental DNA techniques are continuously demonstrating their efficiencies over traditional survey methods for detecting rare species. Unionids have a need for focused conservation efforts as they represent some of the most imperiled aquatic species in North America. Freshwater mussels are notoriously difficult to detect using traditional sampling techniques due to their cryptic morphological features, benthic habitat use, and low densities. Further, the persistence of freshwater mussel populations requires that viable fish host species be present during spawning. Therefore, improved conservation tools are needed to detect and monitor both the imperiled unionids as well as their associated fish host species. Here, we developed novel quantitative PCR (qPCR) assays for the detection of the endangered Texas hornshell (Popenaias popeii) and two of its' host species, the gray redhorse (Moxostoma congestum) and blue sucker (Cycleptus elongatus), which are also species of greatest conservation need in New Mexico. All qPCR assays were highly sensitive, species‐specific, and ultimately validated using eDNA samples collected from streams. These assays offer new tools for managers to detect, monitor, and conserve these imperiled species using environmental DNA.